AGS Report on Engagement Related to the NIH Inclusion Across the Lifespan Policy. Issue 2 (29th January 2019) - Vaughan, Camille P.; Dale, William; Allore, Heather G.; Binder, Ellen F.; Boyd, Cynthia M.; Bynum, Julie P.W.; Gurwitz, Jerry H.; Lundebjerg, Nancy E.; Trucil, Daniel E.; Supiano, Mark A.; Colón‐Emeric, Cathleen
Abstract : After passage of the 21st Century Cures Act, the National Institutes of Health held a workshop in 2017 to consider expanding its inclusion policy to encompass individuals of all ages. American Geriatrics Society (AGS) leaders and members participated in the workshop and formal feedback period. AGS advocacy clearly impacted the resulting workshop report and Inclusion Across the Lifespan policy that eliminates upper‐age limits for research participation unless risk justified and changes the language used to describe older adults and other vulnerable groups. AGS recommendations that were not specifically stated in the updated policy were to encourage active recruitment of older adults, add standard measures of function and/or frailty, and change review criteria to ensure the health status of a study population mirrors typical clinical populations. The updated inclusion policy ultimately offers academic geriatrics programs the opportunities to expand knowledge about health in aging and to continue to provide leadership for research and advocacy efforts on behalf of older adults.J Am Geriatr Soc 67:211–217, 2019. Abstract : See related Editorial byGeorge Kuchel in this issue.